2016
DOI: 10.1002/14651858.cd011745.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive pharmacotherapy for prevention of sudden cardiac death in hypertensive individuals

Abstract: Although antihypertensive drugs reduce the incidence of fatal and non-fatal myocardial infarction, they do not appear to reduce the incidence of sudden death. This suggests that sudden cardiac death may not be caused primarily by acute myocardial infarction. Continued research is needed to determine the causes of sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Several studies have established the benefits of antihypertensive drugs in reducing cardiovascular morbidity and mortality in patients with hypertension [26,27]. However, a recent systematic review in hypertensive patients found that antihypertensive drugs (mainly thiazide diuretics) did not reduce SCA risk (RR 0.96; 95%CI 0.81-1.15), although these drugs did significantly reduce nonfatal and fatal myocardial infarction (MI) compared to placebo or no treatment [28]. However, this study had the limitation that the cause of SCA was unknown.…”
Section: Figurementioning
confidence: 99%
“…Several studies have established the benefits of antihypertensive drugs in reducing cardiovascular morbidity and mortality in patients with hypertension [26,27]. However, a recent systematic review in hypertensive patients found that antihypertensive drugs (mainly thiazide diuretics) did not reduce SCA risk (RR 0.96; 95%CI 0.81-1.15), although these drugs did significantly reduce nonfatal and fatal myocardial infarction (MI) compared to placebo or no treatment [28]. However, this study had the limitation that the cause of SCA was unknown.…”
Section: Figurementioning
confidence: 99%
“…However, there has been debate around whether these guidelines were supported by evidence [10]. The existing systematic reviews and meta-analyses have focused on the efficacy of blood-pressure lowering [5,[11][12][13][14] rather than long-term outcomes [15][16][17].The primary objective of the present review was to compare the efficacy of monotherapy with the thiazide diuretic bendroflumethiazide vs. the thiazide-like diuretic indapamide as a first line in the treatment of primary hypertension on mortality and cardiovascular outcomes. The secondary objective was to compare the effect of these two monotherapies on secondary outcomes such as BP lowering, the need for intensification of treatment and medication discontinuation.…”
mentioning
confidence: 98%
“…However, previous studies did not focus on prevention of SCD by anti-hypertensive treatment. A recent comprehensive meta-analysis by Taverny et al[31] is the only meta-analysis, which focused on the SCD outcome. Strikingly, Taverny et al[31] showed that while HTN treatment reduces the incidence of fatal and non-fatal myocardial infarction (MI), antihypertensive drugs do NOT reduce the incidence of SCD.…”
mentioning
confidence: 99%
“…A recent comprehensive meta-analysis by Taverny et al[31] is the only meta-analysis, which focused on the SCD outcome. Strikingly, Taverny et al[31] showed that while HTN treatment reduces the incidence of fatal and non-fatal myocardial infarction (MI), antihypertensive drugs do NOT reduce the incidence of SCD. Taverny et al[31] included RCTs that compared first line antihypertensive drugs to placebo or control (no therapy).…”
mentioning
confidence: 99%
See 1 more Smart Citation